Analysis of Air Quality and Health Co-Benefits under Low Carbon Pathway in Taiwan - Hsin-Chih Lai; Shih-Ming Chung; Li-Ling Li; Wen-Yinn Lin; Min-Chuan Hsiao (Aerosol and Air Quality Research)
Abstract Climate change has been proven to have adverse effects on human health and ecosystems, especially, the continuous increase in greenhouse gas emissions that are able to drive extreme weather events around the world. Besides greenhouse gas emissions and air pollution also have a mutual relationship. The PM2.5 concentration has been decreasing year by year, but the ozone concentration has been slowly increasing, indicating that ozone issues will be a focus of concern in Taiwan in the future. Therefore, this study focuses on air pollution and its health impacts on power generation on climate change scenario. The air quality in 2050 was estimated in this study by using the Long-range Energy Alternatives Planning System (LEAP) model and the Weather Research and Forecasting-Community Multiscale Air Quality Modeling (WRF-CMAQ) system. The future power plants’ emissions were calculated by historical inventory and the power generation from 2010 to 2016. The simulation results revealed the low-carbon path in the electricity industry can lead to some improvements in air quality and also the associated health benefits. This study demonstrates that implementing carbon reduction strategies in the power sector would lead to a slight increase in ozone concentration. In detail, the annual PM2.5 concentrations would decrease by 0.7 µg m–3 (4%) from BAU (Business As Usual) scenario, while the O3 concentrations would have an increase of 0.3 ppb (1%). The reduction of air pollution can prevent 1012 (374–2463) deaths, saving around 48.9 billion NTD in health monetary costs. In the short term, it is projected that there may be a decrease of 45 patients hospitalized due to respiratory diseases and 53 patients hospitalized due to cardiovascular diseases. Moreover, the reductions in the power sector are expected to have more significant impacts in densely populated areas due to their combination of industrial and residential zones.